1992
DOI: 10.1177/002199839202601103
|View full text |Cite
|
Sign up to set email alerts
|

A Parametric Study of Variables That Affect Fiber Microbuckling Initiation in Composite Laminates: Part 1-Analyses

Abstract: The objectives of this research focus on the effects of nonlinear matrix constitutive behavior, initial fiber waviness, and fiber/matrix interfacial bond strength on fiber microbuckling initiation in thermoplastic composites. Nonlinear geometric and non linear material two-dimensional finite element analysis is used to model the initiation of fiber microbuckling of an initially wavy fiber. Results show that reductions in the resin shear tangent modulus, larger amplitudes of initial fiber wavinesses, and debond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(44 citation statements)
references
References 52 publications
0
42
0
Order By: Relevance
“…We have intentionally chosen to present the computations for model generic material systems only. Some comparisons with available experimental data were discussed earlier [10,[22][23][24]. The applicability of the method to practical materials, e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have intentionally chosen to present the computations for model generic material systems only. Some comparisons with available experimental data were discussed earlier [10,[22][23][24]. The applicability of the method to practical materials, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…From the early literature on compressive fracture, it was easy to get the impression that fibre instability (microbuckling) and kinking are competing mechanisms. However, it is now accepted that a kink band is an outcome of the microbuckling failure of actual fibres, as observed experimentally [23,24]. Fibre microbuckling occurs first, followed by propagation of this local damage to form a kink band.…”
Section: On Analytical Models For Microbucklingmentioning
confidence: 96%
“…Hence, it was implicitly assumed that fibre distribution within the matrix is uniform (no resin rich regions were considered). For resin rich regions, distribution of strain/stresses is disturbed, thus it may trigger premature fibre microbuckling and subsequent kink band formation [15,22].…”
Section: Discussionmentioning
confidence: 99%
“…Following Rosen [3] and many other investigators we employ the Cartesian two dimensional model shown in Figure 1 behavior of the resin but did not explicitly address the variation of the matrix shear strain parallel to the fiber direction, which is incorporated herein. On the other hand, it appears that the finite element method employed by Guynn et al [10] and the iterative numerical scheme utilized by Highsmith et al…”
Section: Ini Rodumtonmentioning
confidence: 99%
“…The probability density distribution which corresponds to equation (26) is The Compressive Resoonse with Randomly Spaced Fibers The probability density AV() given in equation (27) was incorporated into the formulation expressed in equations (11) and (13) and employed to predict the compressive response of Gr/PEEK (APC-2) composite with Vf = 0.6 at a temperature of T = 21 C. Based upon the data of Guynn et al [10], the nonlinear shear behavior of the PEEK resin was fitted by a Ramberg-Osgood expression …”
Section: -2ghmentioning
confidence: 99%